2023
DOI: 10.3390/plants12061281
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Species Change Plant Community Composition of Preserved Prairie Pothole Wetlands

Abstract: Plant communities in North American prairie pothole wetlands vary depending on hydrology, salinity, and anthropogenic disturbance in and around the wetland. We assessed prairie pothole conditions on United States Fish and Wildlife Service fee-title lands in North Dakota and South Dakota to improve our understanding of current conditions and plant community composition. Species-level data were collected at 200 randomly chosen temporary and seasonal wetland sites located on native prairie remnants (n = 48) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The rise of invasive cattails and reed canary grass in shallow-marsh and wet-meadow zones has been observed in other studies within the region as well [94,104]. Jones, 2022, [74]) found that for many wetlands restored in North Dakota where heavily invaded by non-native cool season grasses, this was likely attributed to weak, natural wetland seed banks and mechanically seeding the upland areas to cool season gasses that make up dense nesting cover. While the observed loss of vegetation structure and native species and increases in invasive species in prairie-pothole wetland plant communities appears to be a common pattern, the response of aquatic animal communities to habitat simplification has been less predictable [54], although shifts in aquatic plant communities would affect other organisms within these wetlands [119,120].…”
Section: Evidence For Ecosystem Homogenizationmentioning
confidence: 64%
See 2 more Smart Citations
“…The rise of invasive cattails and reed canary grass in shallow-marsh and wet-meadow zones has been observed in other studies within the region as well [94,104]. Jones, 2022, [74]) found that for many wetlands restored in North Dakota where heavily invaded by non-native cool season grasses, this was likely attributed to weak, natural wetland seed banks and mechanically seeding the upland areas to cool season gasses that make up dense nesting cover. While the observed loss of vegetation structure and native species and increases in invasive species in prairie-pothole wetland plant communities appears to be a common pattern, the response of aquatic animal communities to habitat simplification has been less predictable [54], although shifts in aquatic plant communities would affect other organisms within these wetlands [119,120].…”
Section: Evidence For Ecosystem Homogenizationmentioning
confidence: 64%
“…Non-native grasses, primarily smooth brome (Bromus inermis) and Kentucky bluegrass (Poa pratensis), have invaded many remaining grasslands in the region [71][72][73]. Even in areas where wetlands and grasslands are restored, the revegetation of wetlands is limited to occurring seedbanks and the seeding of upland grass seed mixes [74]. In North Dakota, the absence of wetland-specific seed mixes during restoration has likely facilitated the replacement of native vegetation with non-native cool season grasses and other invasive species [74].…”
Section: Mechanisms For Ecosystem Homogenization In the Pprmentioning
confidence: 99%
See 1 more Smart Citation
“…The markers that differentiate T. angustifolia from T. latifolia will have important applications in North America, where the two species interbreed across a large area and produce an invasive interspecific hybrid (T. × glauca) that dominates wetlands, alters nutrient cycling, and reduces biodiversity across the Great Lakes Region (Bansal et al, 2019); additionally, this hybrid is expanding throughout the Prairie Pothole Region, causing native plant diversity to decrease in invaded potholes (Jones et al, 2023), and may impact essential habitat for millions of breeding and migratory waterfowl species (Tangen et al, 2022). Until now, molecular resources to differentiate T. angustifolia, T. latifolia, and T. × glauca were limited to sets of relatively few individual markers that have produced important insights: RAPDs, chloroplast DNA sequences, and codominant SSR loci have contributed to exposing the sexual fertility of first-generation hybrids (F1) (Snow et al, 2010), asymmetric hybridization (with T. angustifolia being mainly the maternal parent) (Ball & Freeland, 2013;Kuehn et al, 1999;Pieper et al, 2017), overall comparable levels of sexual and clonal reproduction in parents and F1s (Pieper et al, 2020;Travis et al, 2011), heterosis in F1s (Bunbury-Blanchette et al, 2015Travis et al, 2010;Zapfe & Freeland, 2015), a high frequency of F1s in natural populations (Kirk et al, 2011;Travis et al, 2010), and partial sterility of F1s coupled with hybrid breakdown of F2s and advanced-generation hybrids (Bhargav et al, 2022;Pieper et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T. domingensis is increasingly invading regions in Nigeria (Ringim et al, 2016), Costa Rica (Trama et al, 2017) and North America, potentially expanding its range across the latter (Spencer & Vincent, 2013;Zhang et al, 2008). However, the taxonomic identity of these plants is unclear--Are they hybrids, non-native lineages, native lineages responding to environmental change, or misidentified T. angustifolia (Bansal et al, 2019) The markers that differentiate T. angustifolia from T. latifolia will have important applications in North America, where the two species interbreed across a large area and produce an invasive interspecific hybrid (T. × glauca) that dominates wetlands, alters nutrient cycling and reduces biodiversity across the Great Lakes Region (Bansal et al, 2019); additionally, this hybrid is expanding throughout the Prairie Pothole Region, causing native plant diversity to decrease in invaded potholes (Jones et al, 2023), and may impact essential habitat for millions of breeding and migratory waterfowl species (Tangen et al, 2022). Until now, molecular resources to characterise T. angustifolia, T. latifolia and T. × glauca were limited to sets of relatively few individual markers that have produced important insights:…”
Section: Discussionmentioning
confidence: 99%